Carbon bowl and preparation method

By using sandy carbon pellets in water-scarce areas in the Middle East, using a combination of glass fiber cloth and silica solution, a carbon pellet with excellent breathability and blocking water penetration was prepared, which solved the problems of water scarcity and plant growth needs, and achieved efficient utilization of water resources and healthy growth of plants.

CN118930160BActive Publication Date: 2025-03-18ZHUCARBON NEW MATERIALS (SHENZHEN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411219715.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-03-18
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The lack of water resources in the Middle East has led to waste of water resources and increased costs when planting green plants. It is difficult for the existing technology to effectively save water and meet plant growth needs.

Method used

A sandy carbon-building bowl is used to soak it in a silica solution through a glass fiber cloth for wetting. The sand, cement and water are mixed into a slurry in a specific proportion, and applied to the wetted glass fiber cloth surface, and prepared by superposition and extrusion to form a carbon-building bowl with excellent breathability and blocking moisture penetration.

Benefits of technology

It achieves both breathability and strength of the sandy carbon-building bowl, with a V-level breathability level, low water permeability coefficient, effectively saves water, reduces moisture loss, and improves the resistance to lodging and transpiration of plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A sandy carbon-building bowl is prepared by soaking glass fiber cloth in a silica solution for wetting, mixing sand and cement with water into a slurry, brushing it on the surface of the wetted glass fiber cloth, stacking the glass fiber cloth and laying it in a carbon-building bowl mold, brushing the slurry once along the inner wall of the mold, and then standing to dry. The present invention uses local materials, prepares slurry with sand and cement in the desert, brushes it on the surface of the glass fiber cloth wetted with silica, and then prepares the carbon-building bowl by multi-layer stacking. The structure is thin, but has excellent mechanical strength, with a maximum bending strength of 39MPa, and excellent air permeability, with an air permeability grade of V and a water permeability coefficient as low as 0.3×10 ‑7 m / s, effectively blocking moisture penetration and preventing moisture diffusion, thereby reducing moisture loss and achieving the excellent effect of being breathable and waterproof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon building bowl preparation, in particular to a carbon building bowl and a preparation method thereof. Background Art

[0002] In sharp contrast to the abundance of oil resources, the Middle East is extremely short of water resources. The Middle East has a dry climate, few rivers, and large areas of desert without rivers. The lack of water resources seriously affects the lives and production of the people in the Middle East. With the growth of population and economic development, the shortage of water resources in the Middle East is becoming more and more serious. The contradiction in the allocation of water resources in rivers and lakes is also one of the reasons for the tension in the Middle East. The Middle East has adopted the method of increasing revenue and reducing expenditure to solve this problem, such as building water conservancy, desalination of seawater, and water storage in water towers to increase water storage and achieve the effect of increasing revenue. For the planting of green plants, due to the scarcity of water resources, in order to save water resources, it is usually necessary to manually set drainage holes, manually control drainage, or set up complex water storage or irrigation facilities, and agree to infiltration irrigation at a specified time to achieve the purpose of saving water, but these methods cannot completely reject the waste of water resources in the process of cultivating plants, and also increase the investment of other costs. The maintenance cost of a tree in the Middle East is in units of 10,000. Summary of the invention

[0003] In order to solve the problem of water shortage, the present invention aims to provide a sandy carbon pot. The carbon pot is a plant planting container, which is made from local materials, with desert sand as the main raw material. The carbon pot has excellent air permeability and reduces water penetration, which plays a role in saving water and meets the growth needs of plants.

[0004] The second object of the present invention is to provide a method for preparing the above-mentioned carbon-making pot sand.

[0005] The third object of the present invention is to provide an application of the above-mentioned carbon-making bowl.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A sandy carbon-building pot, characterized in that glass fiber cloth is soaked in a silicon dioxide solution for wetting, sand and cement are mixed with water to form slurry, which is applied to the surface of the wetted glass fiber cloth, the glass fiber cloth is stacked and laid in a carbon-building pot mold, the slurry is applied once along the inner wall of the mold, and then it is left to dry.

[0008] Furthermore, the sand is a mixture of coarse sand with a particle size of 0.16-0.25 mm and fine sand with a particle size of less than 0.12 mm, with the mass proportion of the coarse sand being 70-80% and the mass proportion of the fine sand being 20-30%.

[0009] Furthermore, the mass ratio of mixed sand, cement and water in the slurry is 3~4:0.5:3~5.

[0010] Furthermore, the wetting is to immerse the glass fiber in a 25% mass concentration silica solution for 20 to 30 minutes. The silica solution is a 25% mass concentration solution prepared from mesoporous silica particles with an average particle size of 150 nm.

[0011] Furthermore, the stacking of the glass fiber cloths is specifically performed by coating both sides of the wetted glass fiber cloths with a layer of slurry, and 5 to 8 glass fiber cloths coated with slurry are stacked at an angle of 20 to 36 degrees with their centers overlapping.

[0012] A method for preparing sand for carbon potting, characterized in that glass fiber cloth is soaked in a silicon dioxide solution for wetting, sand and cement are mixed with water to form a slurry, which is applied to the surface of the wetted glass fiber cloth, the glass fiber cloth is stacked and laid in a carbon potting mold, and after extrusion, the slurry is applied once along the inner wall of the mold, and then left to dry.

[0013] Furthermore, the sand is a mixture of coarse sand with a particle size of 0.16-0.25 mm and fine sand with a particle size of less than 0.12 mm, with the mass proportion of the coarse sand being 70-80% and the mass proportion of the fine sand being 20-30%.

[0014] Furthermore, the mass ratio of mixed sand, cement and water in the slurry is 3.5~4:0.5:3~5.

[0015] Furthermore, the wetting is to immerse the glass fiber cloth in a silica solution with a mass concentration of 25% for 20 to 30 minutes.

[0016] The silicon dioxide solution is a solution with a mass concentration of 25% prepared from mesoporous silicon dioxide particles with an average particle size of about 150 nm.

[0017] Furthermore, the stacking of the glass fiber cloths is specifically performed by coating both sides of the wetted glass fiber cloths with a layer of slurry, and 5 to 8 glass fiber cloths coated with slurry are stacked at an angle of 20 to 36 degrees with their centers overlapping.

[0018] In order to achieve air permeability and water-tightness, the first thing to consider is the reasonable formulation of the slurry. In order to ensure that the carbon-building pot is air permeable, the amount of mixed sand in the slurry of the present invention far exceeds that of cement. However, such a slurry will make the final carbon-building pot have lower strength and poor structural stability. However, if the amount of cement is increased, the air permeability of the carbon-building pot will deteriorate.

[0019] Under the premise of maintaining the proportion of sand in the slurry, there are differences in the coarse sand and fine sand particle size in the mixed sand of the present invention. By the preparation of coarse sand and fine sand, the slurry is prepared and coated on the surface of the glass fiber cloth, and evenly distributed pores are formed, which is helpful for ventilation. Secondly, after the glass fiber cloth is soaked and moistened by the silicon dioxide solution, the mesoporous silica is attached to the surface of the glass fiber cloth. After brushing the slurry, the silicon dioxide becomes a good adhesive, and the silicon oxygen is combined by forming a silicon-oxygen bond between the particles, and the slurry is firmly fixed on the surface of the glass fiber cloth. By superimposing over-extrusion, the silicon dioxide between the two layers of glass fiber cloth is further embedded in the pores formed by the mixed sand of the slurry, and the gap is further divided to form a uniform distribution of micropores of a certain diameter, and then combined with a multi-layer superimposed structure, while achieving good air permeability, the rapid penetration of moisture is blocked. In addition, the glass fiber cloth after wetting is superimposed after brushing the slurry, which plays a skeleton role, enhances the strength of the carbon bowl prepared, and improves the stability of the carbon bowl.

[0020] A method for preparing a carbon pot, characterized in that it comprises the following steps:

[0021] (1) Mix coarse sand and fine sand to form mixed sand, mix the mixed sand and cement, add water and stir to form a slurry, wherein the coarse sand particle size in the mixed sand is 0.16-0.25 mm, accounting for 70-80% by mass, the fine sand particle size is less than 0.12 mm, accounting for 20-30% by mass, and the mass ratio of the mixed sand, cement and water is 3.5-4:0.5:3-5;

[0022] (2) soaking the glass fiber cloth in a silica solution for 20 to 30 minutes to wet it, wherein the silica solution is a solution with a mass concentration of 25% prepared from mesoporous silica particles with an average particle size of 150 nm;

[0023] (3) Brush a layer of slurry on the inner surface of the carbon bowl mold, and apply a layer of slurry on both sides of the moistened glass fiber cloth. Use 5 to 8 sheets of glass fiber cloth coated with slurry at an angle of 20 to 36 degrees, overlap the center, and then place them in the mold. Place them against the inner wall of the mold and squeeze them evenly in the direction perpendicular to the inner wall. Finally, brush a layer of slurry along the inner wall of the mold, place the mold in a ventilated place to dry naturally, and then remove the mold.

[0024] The above-mentioned carbon pot is used in planting plants, specifically as a container for planting plants.

[0025] During the long-term use of the sand to build carbon pots for planting plants, the silica in the outermost layer of the pot will be slowly released, which will play an anti-lodging role. At the same time, it can also improve the plant's resistance to transpiration and reduce the plant's loss of water.

[0026] The present invention has the following technical effects:

[0027] The present invention uses local materials, prepares slurry with sand and cement from the desert, and applies it on the surface of glass fiber cloth moistened with silicon dioxide. The carbon bowl prepared by multi-layer stacking has a light and thin structure, but has excellent mechanical strength, with a maximum bending strength of 39MPa. At the same time, it has excellent air permeability, with an air permeability grade of V and a water permeability coefficient as low as 0.3×10 -7 m / s, effectively blocking moisture penetration and preventing moisture diffusion, thereby reducing moisture loss and achieving the excellent effect of being breathable and waterproof. DETAILED DESCRIPTION

[0028] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0029] Example 1

[0030] The preparation method of the carbon bowl comprises the following steps:

[0031] (1) Mix coarse sand and fine sand to form mixed sand, mix the mixed sand and cement, add water and stir to form a slurry, wherein the coarse sand particle size in the mixed sand is 0.16-0.25 mm, accounting for 75% by mass, the fine sand particle size is less than 0.12 mm, accounting for 25% by mass, and the mass ratio of mixed sand, cement and water is 3.8:0.5:4;

[0032] (2) soaking the glass fiber cloth in a silica solution for 25 minutes to wet it, wherein the silica solution is a solution with a mass concentration of 25% prepared from mesoporous silica particles with an average particle size of 150 nm;

[0033] (3) Apply a layer of slurry on both sides of the moistened glass fiber cloth, apply a layer of slurry on the inner surface of the carbon bowl mold, use 6 pieces of glass fiber cloth coated with slurry at an angle of 30°, overlap the centers, and then place them in the mold, place them against the inner wall of the mold, and squeeze them evenly in the direction perpendicular to the inner wall. Finally, apply a layer of slurry along the inner wall of the mold, place the mold in a ventilated place to dry naturally, and then remove the mold.

[0034] The water permeability coefficient and air permeability evaluate the water permeability and air permeability respectively. The water permeability coefficient refers to the ability of water to flow through the concrete material per unit area per unit time. The larger the water permeability coefficient, the better the water permeability of the concrete material. The calculation formula of the water permeability coefficient is:

[0035] K=Q / (A×H)

[0036] Where K is the water permeability coefficient, Q is the water flow rate through the concrete material per unit time, A is the cross-sectional area of ​​the material specimen, and H is the material thickness. The water permeability coefficient is one of the important indicators for evaluating the water permeability of concrete materials. Generally speaking, the water permeability coefficient is greater than 1.0×10 -7 m / s can be considered as a concrete material with good permeability.

[0037] The air permeability method is a method to determine the air permeability of a material by measuring the flow rate of gas inside the material. During the test, the material sample needs to be placed in the air permeability tester, and then the gas flow and pressure difference are measured by adjusting the air pressure difference, and finally the air permeability value is calculated.

[0038] The evaluation criteria for the air permeability of concrete materials are mainly the air permeability index. According to the national standard GB / T 50082-2009, the air permeability of concrete is divided into five levels: I, II, III, IV, and V. The smaller the air permeability value, the better the air permeability. Water is used to replace the silica solution to soak the glass fiber cloth. The remaining steps are the same as those in the embodiment. The prepared carbon-building pot is recorded as CK1. The glass fiber cloth is superimposed at an angle of 45°. The remaining steps are the same as those in Example 1. The prepared carbon-building pot is recorded as CK2. The air permeability, water permeability and compressive strength of the carbon-building pots prepared in CK1, CK2 and Example 1 are tested. The results are shown in Table 1.

[0039] Table 1: Air and water permeability indexes of carbon bowls made of different sands

[0040]

[0041] As can be seen from the above table, since CK1 did not use silica solution for soaking and wetting, there was no adhesive effect during the glass fiber cloth stacking process. Due to the high sand content in the slurry, the interlayer bonding force was weak, and the overall strength of the carbon-building bowl was not ideal. Without silica filling, the pores between the glass fiber cloth layers were both water-permeable and air-permeable. In the carbon-building bowl prepared in CK2, since the glass fiber cloth stacking angle was not appropriate, although the effect of air permeability and water-tightness could be achieved, the compressive strength was also poor. In the present invention, the glass fiber cloth was soaked and wetted with silica solution and then stacked at a certain angle to obtain a carbon-building bowl with a flexural strength of 39 MPa, and the water permeability coefficient was significantly reduced by an order of magnitude, which not only achieved air permeability and water-tightness, but also ensured the structural strength of the carbon-building bowl and had good stability in use.

[0042] The sand-made carbon pot prepared in Example 1 can be used for long-term planting of plants in hot and arid areas in the Middle East, and has a stable structure without deformation.

[0043] Example 2

[0044] The preparation method of the carbon bowl comprises the following steps:

[0045] (1) Mix coarse sand and fine sand to form mixed sand, mix the mixed sand and cement, add water and stir to form a slurry, wherein the coarse sand particle size in the mixed sand is 0.16-0.25 mm, accounting for 70% by mass, the fine sand particle size is less than 0.12 mm, accounting for 30% by mass, and the mass ratio of the mixed sand, cement and water is 3.5:0.5:3;

[0046] (2) soaking the glass fiber cloth in a silica solution for 20 minutes to wet it, wherein the silica solution has a mass concentration of 25% prepared by mesoporous silica particles with an optimal particle size of 150 nm;

[0047] (3) Apply a layer of slurry on both sides of the moistened glass fiber cloth, apply a layer of slurry on the inner surface of the carbon bowl mold, use 8 sheets of glass fiber cloth coated with slurry at an angle of about 22°, overlap the centers, and then place them in the mold, place them against the inner wall of the mold, and squeeze them evenly in the direction perpendicular to the inner wall. Finally, apply a layer of slurry along the inner wall of the mold, place the mold in a ventilated place to dry naturally, and then remove the mold.

[0048] After testing, the carbon bowl prepared in this embodiment has a light and thin structure, high strength, reaching 37MPa, and a water permeability coefficient of 0.03×10 -7 m / s, and the air permeability grade reaches grade V. The sand-made carbon pot prepared in Example 2 can be used for long-term planting of plants in hot and arid areas in the Middle East, and the structure is stable and does not deform.

[0049] Example 3

[0050] The preparation method of the carbon bowl comprises the following steps:

[0051] (1) Mix coarse sand and fine sand to form mixed sand, mix the mixed sand and cement, add water and stir to form a slurry, wherein the coarse sand particle size in the mixed sand is 0.16-0.25 mm, accounting for 80% by mass, the fine sand particle size is less than 0.12 mm, accounting for 20% by mass, and the mass ratio of the mixed sand, cement and water is 4:0.5:5;

[0052] (2) soaking the glass fiber cloth in a silica solution for 30 minutes to wet it, wherein the silica solution has a mass concentration of 25% prepared by mesoporous silica particles with an optimal particle size of 150 nm;

[0053] (3) Apply a layer of slurry on both sides of the moistened glass fiber cloth, apply a layer of slurry on the inner surface of the carbon bowl mold, use 5 sheets of glass fiber cloth coated with slurry and overlap them at an angle of 36°, then place them in the mold, place them against the inner wall of the mold, squeeze them evenly in the direction perpendicular to the inner wall, and finally apply a layer of slurry along the inner wall of the mold. Place the mold in a ventilated place to dry naturally, and then remove the mold.

[0054] After testing, the carbon bowl prepared in this embodiment has a light and thin structure, high strength, reaching 34MPa, and a water permeability coefficient of 0.06×10 -7 m / s, and the air permeability grade reaches grade V. The sand-made carbon pot prepared in Example 3 can be used for long-term planting of plants in hot and arid areas in the Middle East, and the structure is stable and does not deform.

Claims

1. A method for preparing a sandy carbon-building pot, characterized in that: The method comprises soaking glass fiber cloth in a silicon dioxide solution for wetting, mixing sand and cement with water into a slurry, and brushing the slurry on the surface of the wetted glass fiber cloth, stacking the glass fiber cloth and laying it in a carbon pot mold, and after extrusion, brushing the slurry once along the inner wall of the mold, and then standing to dry. The sand is a mixed sand composed of coarse sand with a particle size of 0.16-0.25 mm and fine sand with a particle size of less than 0.12 mm, the mass proportion of coarse sand is 70-80%, and the mass proportion of fine sand is 20-30%. The mass ratio of mixed sand, cement and water in the slurry is 3.5-4:0.5:3-5. The stacking of the glass fiber cloth is specifically to brush a layer of slurry on both sides of the wetted glass fiber cloth, and 5-8 glass fiber cloths coated with slurry are used at an angle of 20-36° with the centers overlapping and stacked.

2. The method for preparing a carbon-building pot as claimed in claim 1, characterized in that: The wetting is to immerse the glass fiber in a 25% mass concentration silica solution for 20 to 30 minutes. The silica solution is a 25% mass concentration solution prepared from mesoporous silica particles with an average particle size of 150 nm.

3. Use of the carbon pot prepared by the method of claim 2 in growing plants, specifically as a container for growing plants.

Citation Information

Patent Citations

  • Preparation method of novel energy-saving inorganic thermal insulation plate

    CN101891446A

  • Hybrid nanoparticle reinforced ecological pervious concrete and preparation method thereof

    CN111003999A